Analisis Bullwhip Effect Barang Fast Moving Pada Divisi Non Food Soft Line Kategori Haba & Toiletries Studi Kasus Di Assalaam Hypermarket Jl. Ahmad Yani No. 308, Pabelan,Kartasura, Sukoharjo, Jawa Tengah 57102 - HAPSARI, DINI; , Indah Pratiwi ST.,MT (2016)
The core essence of supply chain management is the existence of coordination and synchronization at upstream to downstream, because this coordination between chain in SCM shall go well. One weakness in supply chain management is the flow of information therein. Distortion information taking place in suplly chain management often called bullwhip effect. Material losses bullwhip effect not only on the availability of products alone but also on the cost savings in manufacturing or retailing. In this study calculation bullwhip effect done in assalaam hypermarket located in the kartasura central java. The data used on the first of the data and sales distributors - Assalaam (supplier), the second ism that used data and sales Assalaam (supplier) - Assgros. Using data from assgros Maksum by which is located at Baki Sukoharjo and Assgross Permata which is located in Fajar Indah Karanganyar. The research was done in a division of non food soft line category HABA & Toiletries, calculate the value of bullwhip effect fast moving goods, knowing the main cause of the occurrence of bullwhip and how effect of the proposed fixes from cases bullwhip effect in assalaam hypermarket with data used for 12 in 2015. The method used the theory of Pareto 20/80 for determining the sampel and the bullwhip effect. The treatment using five kinds of products, the five such products processed to know ω. The bullwhip be done with four ω. If the value of the ω show a product the bullwhip effect, data acquisition is forecast to reduce the value bullwhip's going on. The results showed 15 of the bullwhip effect, after forecasting just four things that shows the bullwhip effect.